1982
DOI: 10.1079/bjn19820009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary methyl branched-chain fatty acids on aspects of hepatic lipid metabolism in the rat

Abstract: 1. Rats were fed to appetite on a stock laboratory diet or on diets consisting of the stock diet and in addition 50 or 200 g triolein/kg, 50 g palmitic acid/kg or 50 g/kg of a concentrate mixture of methyl branched-chain fatty acids (Me-BCFA) which had been prepared from sheep adipose triacylglycerols.2. No differences could be detected in the APdesaturase activity or fatty acid synthetase activity of liver preparations from rats which had been fed on either the stock diet, the 50 g palmitic acid/kg or the 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…According to these authors, enhanced accumulation of BCFAs in mice liver was associated with decreased steatosis. Finally, the role of SCD1 in the BCFA‐mediated inhibition of TG synthesis in the liver is supported by the results of a groundbreaking research conducted by Wahle and Hare . These authors observed a 50% decrease in the liver activity of SCD1 in rats fed with a BCFA‐rich diet.…”
Section: Discussionmentioning
confidence: 77%
“…According to these authors, enhanced accumulation of BCFAs in mice liver was associated with decreased steatosis. Finally, the role of SCD1 in the BCFA‐mediated inhibition of TG synthesis in the liver is supported by the results of a groundbreaking research conducted by Wahle and Hare . These authors observed a 50% decrease in the liver activity of SCD1 in rats fed with a BCFA‐rich diet.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies noticed lower levels of BCFAs in the serum of excess-weight individuals than in the serum of lean 89 , 90 , and this parameter increased linearly with individual’s weight loss 86 . It is hypothesized that BCFAs are negatively associated with obesity because they inhibit the liver synthesis of triglycerides 89 , 91 . Enzyme propionyl-CoA carboxylase ( pccA ) and MUT play a key role in the synthesis of propionate, another inhibitor of de novo liver lipogenesis 92 .…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the elevated intraperoxisomal acyl-CoA esters compete with the retroconversion steps. Alternatively, the effect is secondary to the massive accumulation of phytanic/pristanic acid (or their CoAesters), given that methylbranched fatty acids have been reported to interfere with fatty acid desaturation (Wahle and Hare, 1982).…”
Section: )mentioning
confidence: 99%